The Effect of Project-Based Learning and Learning Motivation on Rahmatan's Profile Strengthening Lil Alamin in MAN 01 Asahan - Sirait, Trian Azhari Fadilah; Halimah, Siti; Sitorus, Ahmad Syukri (SAINTIS Publishing, 2024)
This study investigates the impact of project-based learning and student motivation on the enhancement of the Rahmatan Lil-Alamin profile at MAN 01 Asahan. The primary objective is to fulfill the requirements for the final assignment and to test theoretical frameworks regarding educational strategies. Employing a quantitative experimental method with a 2x2 factorial design, the research examines how different combinations of project-based learning and varying levels of student motivation affect the development of the Rahmatan Lil-Alamin profile. Results indicate significant interactions between the types of learning approach and motivational levels, demonstrating that both factors collectively contribute to the strengthening of the Rahmatan Lil-Alamin profile. The findings underscore the importance of integrating effective learning strategies with motivational support to achieve educational goals. This research provides valuable insights for educators seeking to enhance character education through targeted pedagogical practices.